Economic Valuation of Water Quality Condition Ogan River against the Clean Water in the District of Ogan Komering Ulu - Enda Kartika Sari; Lucyana Lucyana (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Sari EK, Lucyana L. 2020. Economic valuation of water quality condition ogan river against the clean water in the district of Ogan Komering Ulu. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 139-148. The existence of the Ogan River has experienced a reduction in water quality, this is caused activities from the community such as disposing household waste and dumping industrial waste into the river. This fact causes the need of protecting the quality of Ogan river water by using Perusahaan Daerah Air Minum (PDAM) and shallow wells to fulfill the needs of clean water for the community. The use of shallow wells and PDAM caused economic losses to the community. They raise extra costs or replacement costs that must be paid by the community. The purpose of this study was to determine the community's perception of the impact of river water quality and to determine the cost of replacement by using the replacement cost method that must be spent by the community around the Ogan River Basin Ogan Komering Ulu Regency. The method used descriptive analysis, and a replacement cost approach for a year. The total population of 3,329 is family head (KK). The samples in this study amounted to 149 KK. The perception of people who want to improve the quality of the river Ogan by 90.6 percent and of 88.6 percent of the public said it would remain in the vicinity of the Ogan River despite the condition change or increasingly bad. . In this study was take the reason people remain 51 percent is due to an economic factor. Regarding the economic valuation of clean water aspects, 71.8 percent of the people use PDAM, 25.5 percent use well water and 2.7 percent use river water as a source of clean water. The estimated cost of replacement costs incurred for one year is Rp102,510,000 and the need for clean water is 20,502 m3/year. The total costs incurred by the community amounted to Rp 357,852,500.